Al2O3-MgO Supported Ni, Mo, and NiMo Mixed Phosphidic-Sulphidic Phase for Hydrotreating of Stearic and Oleic Acids Into Green Diesel - Puello-Polo, Esneyder; Arias, Dana; Márquez, Edgar (Frontiers in Chemistry, 2022)
The effect of the sulfur and metal type content of MoP-S/γ-Al2O3-MgO, NiMoP-S/γ-Al2O3-MgO and NiP-S/γ-Al2O3-MgO phosphide on hydroprocessing (HDO, HDCx-HDCn, HCK, HYD and HYG) of fatty acids was studied. The catalysts were characterised by XRF, XRD, textural properties, XPS, Raman, Py-TPD and EDS elemental mapping. The chemical analyses by X-ray Fluorescence (XRF), EDS elemental mapping and CHNS-O elemental analysis showed stoichiometric values Al/Mg= 37, Mo:Ni:P 1 and S (≤ 4.5 wt%, this value means that the molar ratio Mo:S 1.0:1.6, i.e. MoS2); also EDS elemental mapping confirmed the presence of Mo, Ni, Al, O, P, Mg and S with well-distribution on Al2O3-MgO. The impregnation of metals leads to a decrease in the surface area and pore volume as follows NiMoP-S/γ-Al2O3-MgO < MoP-S/γ-Al2O3-MgO < NiP-S/γ-Al2O3-MgO < Al2O3-MgO < Al2O3 (unimodal pore size distribution), propitiating a pseudo bimodal pore size distribution with Dp-BJH between 5-7 nm and 11.8-14.2 nm. XRD confirmed differences between metallic phosphates and phosphides and XPS the presence at the surface of Moδ+(0< δ+ <2), Mo4+, Mo6+, Niδ+(0< δ+ <2), Ni2+, S2-, SO42-, Pδ- and P5+ species. Raman revealed the presence of MoS2 in MoP-S/γ-Al2O3-MgO and NiMoP-S/γ-Al2O3-MgO, while The NiMoP-S/γ-Al2O3-MgO catalyst has a more significant number of Brønsted and Lewis sites, although the increasing temperature decreases the Lewis sites. MoP-S/γ-Al2O3-MgO was more active at HDO, showing the highest production rate for octadecane of 52.8 mol/(gcat·h), whereas NiP-S/γ-Al2O3-MgO was more active at HDCx-HDCn (44.7 mol/(gcat·h)) and HCK (6.2 mol/(gcat·h)), and NiMoP-S/γ-Al2O3-MgO had a mix of HDO (47.0 mol/(gcat·h)) and HDCx-HDCn (40.9 mol/(gcat·h)). This showed production towards octadecane, heptadecane and light hydrocarbons, meaning that the fatty acids were deoxygenated through of bifunctional sites for hydrogenation (HYD) and hydrogenolysis (HYG) as follows: MoP-S/γ-Al2O3-MgO (K1= 0.08 and K2= 0.03 L/mol) < NiMoP-S/γ-Al2O3-MgO (K1= 0.25 and K2= 0.45 L/mol) < NiP-S/γ-Al2O3-MgO (K1= 2.5 and K2= 6.5 L/mol). We consider that sulfur acts as structural promoters in the catalysts, allowing the largest generation of heptadecane and octadecane by the presence of BRIM sites for HYD and CUS sites for HYG or mixed phosphidic-sulphidic species.